Pengaruh Metode Fabrikasi terhadap Kekuatan Tarik Komposit Serat Cordyline Australis: The Effect Of Fabrication Method On The Tensile Strength Of Cordyline Australis Fiber Composites - Ida Bagus Putu Purwadnyana; Tjokorda Gde Tirta Nindhia (Universitas Pendidikan Ganesha, 2025)
This study aims to investigate the effect of fabrication methods on the tensile strength of epoxy composites reinforced with untreated Cordyline australis fibers. Two fabrication methods were compared: closed hand lay-up and vacuum chamber. The fiber weight fractions used were 1%, 2%, and 5%. Tensile tests were conducted according to ASTM D638, and morphological characteristics were examined through surface and fracture micrograph analysis. The results show that the hand lay-up method consistently produced higher tensile strength compared to the vacuum method across all fiber fractions. The highest tensile strength was achieved at 2% fiber fraction using the hand lay-up method, reaching 26.91 MPa, while the vacuum method only reached 21.11 MPa. At 5% fiber content, the vacuum method experienced a significant drop in tensile strength to 12.34 MPa, indicating its ineffectiveness at higher fiber loadings without treatment. Micrographic analysis revealed that the vacuum method tended to produce voids and resin-poor areas around the fibers. These findings confirm that fabrication method has a significant influence on the mechanical performance of the composite, and that the hand lay-up method is more suitable for natural fiber-based composites without additional treatments.